(untitled) (Research, Society and Development, 2018)
The history of education of Rio Grande do Norte has been written and rewritten according a diversity of views and prospects. Each work, beyond yours analytics contributions, shows on a direct or indirect way, occasionally or intentionally, the author´s view of world, their place of speech and the way like conceive the educational past. This work has like objective make reflections about the writing process of history about the norte-rio-grandense education, specifically the primary teaching, since the empire to the first republic, from the works of two intellectuals: Maria Marta de Araújo and Nestor dos Santos Lima. We work with the master´s dissertation produced for the first, with the title “Origin and attempts of organization of the scholarly net of Rio Grande do Norte: from the colony to the first republic”, presented at UNICAMP/ SP in 1979. About this work we emphasize the chapters II, III e IV, relating to our temporal cutting. With relation to Nestor Lima, we assay the book with the title “One century of primary teaching”, produced in 1927 in celebration to the centennial of the law of October 15, 1827, which broach the organization of the primary teaching and the creation of schools at mains cities and villages of the empire. We make relations of the two authors based on Michel de Certeau discussions in “The writing of History”, producing a historiographical analysis attentive to sources used, the form and the intentions of their writing, the place occupied by each author and their intelectual affiliation. Finally, we dialogue also with the sociologist Pierre Bourdieu, about the concepts of field and habitus, to understand better the relations that within the process of the history´s writing and production of a field relative to the educational history of Rio Grande do Norte. This discussion guide us, therefore, to the observation of different views about the educational past of the state, which are oriented by the place of speech of each author and also by the intention of their work and social and intellectual relations in the process of the educational history writing norte-rio-grandense.